The Influence of Acceptance of RAISA (Robots, Artificial Intelligence, And Service Automation) Technology on Intentions to Use Technology and Intentions to Visit Tourists in Bali - Jaya , I Made Agus Kusuma; Suasapha , Anom Hery; Liestiandre, Hanugerah Kristiono (Journal of Applied Science in Tourism Destination, 2024)
The research aims to see how the effect of acceptance of RAISA technology (Robots, Artificial Intelligence, And Service Automation) by tourists on the intention to use RAISA technology with TAM and the intention to visit in Bali. This research was conducted in Bali with 384 respondents who visited Bali and were traveling in Bali. The analytical technique used is descriptive quantitative and Structural Equation Models. The result found that the ease of use of RAISA technology had a positive effect on the perceived use of RAISA technology. The two constructs also have a positive effect on attitudes towards RAISA. And this positive attitude affects the intention to use RAISA technology and the intention to visit Bali with the RAISA technology. However, the perceived usefulness construct of RAISA technology does not affect foreign tourists and has little effect on domestic tourists. This research will help stakeholder providers to understand tourist attitudes regarding the adoption of RAISA technology in Bali in general. Technology engineers and tourism business owners in implementing RAISA technology for tourism in Bali must pay attention to the ease of use and usefulness. And in the application of RAISA technology, human intervention is still needed in tourism services where current technology is still unable to overcome certain complexities and problems. The government needs relevant regulations regarding RAISA technology and human resource development in Bali. This research is still exploring tourism broadly, not specific to any one service or tourism sector. So further research is needed to explore specifically one technology in RAISA, on a particular sector, perspectives on different types of tourists, and the extent to how far RAISA technology can replace existing jobs.